Educational role of nurses in joining the treatment of Systemic Arterial Hypertension: integrative literature review - Yasmin Fernandes Costa; Ocione Cristina de Araújo; Lucas Bruno Matias de Almeida; Selma Maria da Fonseca Viegas (O Mundo da Saúde)
High blood pressure (HBP) is characterized as a chronic disease with a high prevalence of deaths worldwide. The study aims to describe the educational role of the nurse in compliance to treatment of systemic arterial hypertension. It is an integrative literature review, a method that provides the synthesis of knowledge and incorporation of the applicability of the results of 20 significant studies to the theme. We used the Content Analysis for organizing integrative review of data, and originated four thematic categories that describe the factors that influence adherence to treatment of Systemic Arterial Hypertension (SAH) and the educational role of the nurse for the adherence to people affected by this disease: Systemic Arterial Hypertension: interventions on modifiable risk factors , Health education to control and adherence to treatment of SAH; (Un) knowledge of hypertension disease by the subject; (No) adherence to medication and non-medication. The results show that intervention in the modifiable factors of SAH is based on changing habits and lifestyles that contribute to worsening the disease. Therefore, health education should be prioritized by the nurse, emphasizing the importance of healthy habits. Nurses can stimulate the practice of self-care. Educational practices must meet individual and family needs for greater adherence to medication and non-medication by the subject having SAH. Nurses can contribute significantly to improving the health and quality of life of patients having SAH.